FIRE FIGHTERS' MOBILE PRE-HOSPITAL CARE (193) AND PRESERVATION OF EVIDENCE AT THE CRIME SCENE FROM A CHAIN-OF-CUSTODY PERSPECTIVE (Interdisciplinary Studies Journal, 2023)
This study aimed to analyze the knowledge of fire department mobile pre-hospital care professionals in the handling of traces at crime scenes, from the perspective of the chain of custody. This study was carried out at the Pernambuco Military Fire Brigade, located in Olinda, Pernambuco. Of the 202 military personnel in this corps, all 50 drivers, first responders, and medics made up the study sample. A questionnaire with multiple-choice questions was administered to the professionals on days when they were on duty. The data was analyzed using absolute and percentage frequencies and the Chi-square and Fisher's Exact tests were used to verify associations between categories. The margin of error used was 5%.  It was found that 54% (n=27) of the participants said they had minimal or no knowledge of the Anti-Crime Law and 90% (n=45) did not know what a chain of custody center was. The lack of a specific protocol for attending to and preserving traces was mentioned by 80% (n=40) of the sample. For 78% (n=39) of the professionals, there is a need for further training in the preservation of traces. It can be concluded that these professionals are not trained in the stages of preserving traces, as set out in Law 13.964/19. The lack of protocols and training courses can lead to insecurity and misconduct on the part of professionals. It is imperative to invest in training and continuing education processes so that public agents can recognize an element as being of potential interest to produce expert evidence.
Keywords: Forensic Trace; Chain of Custody; Pre-Hospital Emergency Care